HUBUNGAN GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIFITAS (GPPH) TERHADAP STATUS GIZI ANAK DI KLINIK TUMBUH KEMBANG RSUP SANGLAH DENPASAR - Megapuspita, Gusti Ayu Teja Devi; Windiani, I Gusti Ayu Trisna; Adnyana, I Gusti Agung Ngurah Sugitha (E-Jurnal Medika Udayana; Vol 6 No 8 (2017): E-Jurnal Medika Udayana, 2017)
Attention Deficit/Hyperactivity Disorder (ADHD) consists of a pattern that shows signs of persistent inattention and / or impulsive behavior and hyperactivity, which are heavier than they should occur at the age of development DAss . Children with ADHD have more physical activity than children without GPPH that affect their nutritional status. The aim of this study was to determine the relationship Attention Deficit/Hyperactivity Disorder (ADHD) and nutritional status of children in Growth and Development Clinic Sanglah Hospital. This research method analytical cross-sectional, that taken from the register of children with ADHD in Growth and Development Clinic Sanglah Hospital on January 1, 2014 - August 31, 2016. The results of 120 samples consisting of 48 ADHD children and 72 of  non-ADHD children. The relationships of ADHD with normal and abnormal nutritional status  is significant (PR: 0.5, 95% CI : 0.26; 0.97, p = 0.028), thin and normal nutritional status are also significant (PR: 0.2, 95% CI : 0.48; 0.835, p = 0.001), whereas the obese and normal nutritional status was not significant (PR: 0.875, 95% CI : 0.37; 2.06, p = 0.759). The conclusions of this study there is a significant relationship between ADHD and nutritional status (p = 0.028), where the prevalence of abnormal nutritional status in the children with ADHD is half lower than the children in non-ADHD group.   Keywords : attention deficit and hyperactivity disorders, nutritional status, malnutrition, overweight.